2016
DOI: 10.1016/j.jip.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic structure and habitat associations of Beauveria species isolated from soils in Slovakia

Abstract: The phylogenetic structure of 109 soil-borne entomopathogenic Beauveria isolates acquired using the Galleria mellonella bait method from different habitat types in Slovakia was determined by sequence analysis of their ITS and Bloc loci. Three Beauveria species were identified; Beauveria bassiana, B. pseudobassiana and B. brongniartii, represented by 51.4%, 43.1% and 5.5% of acquired isolates, respectively, which were resolved into 15, 1 and 1 distinguishable haplotypes. Correlation analysis with the habitat ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…While some studies showed a higher abundance of Beauveria bassiana (Balsamo) Vuillemin in soils from hedgerows and Metarhizium anisopliae (Metschnikoff) Sorokin in soils from cultivated fields (Meyling and Eilenberg 2006), others reported a higher abundance of M. anisopliae in marginal soils (Clifton et al 2015). Habitat-specific preferences have also been noticed in the case of some EPF (Bidochka et al 1998, Quesada-Moraga et al 2007, Medo and Cagáň 2011, Medo et al 2016. Knowing the differences in EPF abundances within different habitat-types is important in understanding which fungal species is suitable to and would proliferate in a particular habitat-type (Quesada-Moraga et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies showed a higher abundance of Beauveria bassiana (Balsamo) Vuillemin in soils from hedgerows and Metarhizium anisopliae (Metschnikoff) Sorokin in soils from cultivated fields (Meyling and Eilenberg 2006), others reported a higher abundance of M. anisopliae in marginal soils (Clifton et al 2015). Habitat-specific preferences have also been noticed in the case of some EPF (Bidochka et al 1998, Quesada-Moraga et al 2007, Medo and Cagáň 2011, Medo et al 2016. Knowing the differences in EPF abundances within different habitat-types is important in understanding which fungal species is suitable to and would proliferate in a particular habitat-type (Quesada-Moraga et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Beauveria pseudobassiana is an entomopathogenic fungus with a worldwide distribution, and it can be pathogenic to a wide range of hosts [ 37 , 55 , 56 ]. Recent analyses of soil samples in Slovakia have indicated that B. pseudobassiana prefers forest habitats over field crops or meadows [ 57 ], assumed to be due to its better adaptation to forest ecosystems. It was first described, i.e., distinguished from B. bassiana , in 2011 by DNA-based phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, six in vitro isolates of this species were obtained from the cadavers and thus the fungus cannot be considered a rare EPF in large pine weevil populations. Recent analyses of soil samples in Slovakia indicated that B. pseudobassiana preferred forest habitats over field crops or meadows [62] assuming its better adaptation to forest ecosystems. On the other hand, this species was not identified from forest soil samples in Poland [63].…”
Section: Discussionmentioning
confidence: 99%